An optimal cigarette tax in Malaysia - Mohamed Nor, Norashidah; Raja Abdullah, Nik Mustapha; Rampal, Lekhraj; Mohd Noor, Zaleha (Faculty of Economics and Management, Universiti Putra Malaysia, 2013)
Determination an optimal cigarette excise tax is essential for the government to ensure that price of cigarette after tax is high enough to reduce consumption of cigarette and generate maximum tax revenue to the government. It is timely that government should consider having a specific tobacco control policy funded from earmarking of revenues from cigarette tax increases or “sin tax”. The estimated regression of optimal cigarette tax is based on Laffer curve equation. In this study, the estimated optimal real excise tax rate is 0.216 sen or 0.262 nominal excise tax rate per stick, which is 16.5% higher than the excise tax rate in 2009. The increase in real revenue that can be earned after imposing an optimal excise tax is 18% and 23.6% in the short run and long run respectively. The expected reduction in consumption per capita for cigarette is 6.4% in the short run and 11.6% in the long run.